Break the chain of COVID-19 transmission: Perspective from a cardiologist-in-practice - sidhi laksono purwowiyoto; Budhi Setianto Purwowiyoto (Jurnal Kardiologi Indonesia, 2020)
Indonesia is currently suffering through a pandemic outbreak of severe respiratory syndrome coronavirus 2 (SARS-CoV-2) known as Coronavirus Disease 2019 (COVID-19). Every day this infection raises double, health community is fighting COVID-19 with their armamentarium and policy. Indonesian Heart Association (IHA) has already issued the statement about cardiovascular services during the outbreak of COVID-19. The policy is rescheduling non urgent outpatient visits as necessary, social distancing strategy in outpatient clinic and using personal protective equipment (PPE) in outpatient clinic or during the cardiac examination (echocardiography, cardiac CT, electrophysiology and invasive cardiology). Most of international recommendations have recommended social distancing and reschedule non urgent visits. This document gives a general information about the prevention of COVID-19 in cardiology department.